Factors Affecting the Value of Regional Government Financial Reporting Information - Nengsih, Rita (International Conference on Multidisciplinary Research, 2020)
This study aimed to examine the effects of the quality of human resources, the use of informationtechnology, internal control systems, and regional financial supervision simultaneously and partiallyon the value of financial reporting information for the regional government of Nagan Raya. Thepopulation in this study were 67 employees at the Regional Revenue and Financial Management Officeof Nagan Raya Regency. The data were collected from questionnaires, books and journal articles andanalyzed quantitatively using multiple linear regression. The results showed that the quality of humanresources, the utilization of information technology, internal control, and regional financial controlhad a significantly positive effect on the value of information on financial reporting of the regionalgovernment of Nagan Raya, simultaneously and partially.Keywords: The Quality of Human Resources, Information Technology, Internal Control, FinancialSupervision, Financial Reporting Information.